2024
DOI: 10.3390/foods13020223
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the Appearance and Nutritional Quality of Tomato Fruits Resulting from Foliar Spraying with Silicon

Li Wang,
Ning Jin,
Yandong Xie
et al.

Abstract: Research on silicon (Si), an element considered beneficial for plant growth, has focused on abiotic and biotic stress mitigation. However, the effect of Si on tomato fruit quality under normal growth conditions remains unclear. This study investigated the effects of applying different levels of Si (0 mmol·L−1 [CK], 0.6 mmol·L−1 [T1], 1.2 mmol·L−1 [T2], and 1.8 mmol·L−1 [T3]) in foliar sprays on tomato fruit quality cultivated in substrates, and the most beneficial Si level was found. Compared to CK, exogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Previous research has revealed that biochar incorporation can enhance plant growth, boost crop yields, and improve water use efficiency [ 67 ]. In a study carried out by Wang et al [ 68 ], it was discovered that the incorporation of 50 tons ha − 1 of biochar resulted in a 55% increase in Solanum lycopersicum yield and a 45% improvement in water use efficiency than the control. Biochar treatment prevents membrane damage by reducing Na + level and boosting K + , therefore enhancing leaf hydration status during salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that biochar incorporation can enhance plant growth, boost crop yields, and improve water use efficiency [ 67 ]. In a study carried out by Wang et al [ 68 ], it was discovered that the incorporation of 50 tons ha − 1 of biochar resulted in a 55% increase in Solanum lycopersicum yield and a 45% improvement in water use efficiency than the control. Biochar treatment prevents membrane damage by reducing Na + level and boosting K + , therefore enhancing leaf hydration status during salt stress.…”
Section: Discussionmentioning
confidence: 99%